Interpersonal problems in borderline personality disorder: antecedents, manifestations, and consequences - Hepp, Johanna (2019)
Individuals with Borderline Personality Disorder (BPD) suffer from interpersonal problems, such as frequent conflicts, low levels of relationship satisfaction, and high levels of loneliness. Interpersonal problems in BPD are pervasive and create both a personal and societal burden (e.g. through health care costs and productivity losses). Previous empirical studies suggest that impaired social cognitive processes, an inability to maintain interpersonal cooperation, and functional neurological alterations may underlie these problems. Theories of BPD, such as the Biosocial Model, further emphasize the interplay between interpersonal problems and affective instability, both of which represent core symptoms of the disorder. Specifically, theories of BPD suggest that negative affect can be both an antecedent and a consequence of interpersonal problems. Within this thesis, I conducted two studies to test whether this proposed association holds in the daily lives of individuals with BPD. For this purpose, I utilized Ambulatory Assessment, a method of collecting data in real-life and near real-time via handheld devices such as smartphones. I specifically assessed perceived rejection and disagreement events as manifestations of interpersonal problems. For study 1, I recruited 80 participants with BPD and a clinical control group of 51 participants with depression of dysthymia. Participants were in the study for 28 days and provided data through a handheld device at 6 random time-points throughout the day. At each time-point, participants reported whether they had experienced a rejection or disagreement event since last prompted and rated their level of negative affect, specifically hostility, sadness, and fear. Using multivariate multi-level modeling, I analyzed the concurrent momentary relationship between interpersonal problems and negative affect. Results showed that the rejection-hostility, rejection-sadness, and disagreementhostility associations were significantly stronger in the BPD than in the depressed control group. In an effort to determine the replicability and thus robustness of these findings and to further detail a potential specificity for the BPD population, I attempted replication of these findings in a second study. I again recruited a group of participants with BPD (n = 56) and this time included a control group of individuals from the community with alcohol use (n = 60). The study ran for 21 days with 6 random daily assessments of interpersonal problems and negative affect. Replicating findings from study 1 , the rejection-hostility, rejection-sadness, and disagreement-hostility associations were again significantly stronger in the BPD group. Additionally, study 2 extended the first study by including timelagged analyses. That is, I modelled whether interpersonal problems also predict later levels of negative affect (i.e. on average 2 hours later). Results from the lagged analyses revealed that rejection was associated with subsequent hostility and with subsequent sadness more strongly in the BPD group, as was disagreement with subsequent hostility and fear. Overall, the results from these two studies suggest that interpersonal problems and negative affect may be associated in a mutually reinforcing way (a ‘vicious cycle’) in the daily lives of those with BPD. Future studies could extend these results to further types of negative affect and a broader range of interpersonal problems. They could also consider a potential protective role of positive events and affect. With regard to clinical practice, the results suggest a need for teaching emotion regulation strategies that are applicable in interpersonal contexts and a potential benefit of identifying specific interpersonal events as typical triggers for negative affect. In addition to these two daily life studies, I conducted a third study in which I shifted the focus away from assessing intrapersonal processes of the BPD individual. I posited that interpersonal problems in BPD are not only affected by the BPD individuals themselves but also by their interaction partners. However, processes pertaining to interaction partners have rarely been addressed empirically. In order to fill this gap, I assessed how participants evaluate those with BPD in a first-impression type situation using the ‘Thin Slices’ paradigm. I reasoned that if participants evaluated those with BPD in a systematically negative way, this could contribute to the lack of social bonds and high rates of interpersonal problems. I created a video set of 26 target participants with BPD and 26 healthy control participants who briefly speak about their personal preferences during the video. Next, these videos were shown to two student rater samples, who evaluated targets on the dimensions likeability, trustworthiness, and cooperativeness. Regarding cooperativeness, we specifically asked raters to estimate how much money targets had shared in an economic game (‘dictator game’). We collected actual dictator game contributions from all targets and these did not differ between the groups. Sample 1 saw the videos with audio and sample 2 without audio, so that raters in this sample had to rely solely on visual information. Notably, raters did not have any further information about the targets, including that some of them had BPD. Results showed that raters evaluated BPD targets as less likeable and less trustworthy in both samples and in the second sample also as less cooperative (in the absence of an actual difference in cooperative behavior between the target groups). I concluded that raters must have relied on visual cues to form their evaluations of the presented targets. Based on empirical findings from social and personality psychology, I discussed facial affect display as a likely cue for likeability, trustworthiness, and cooperativeness. Since previous empirical studies have shown that individuals with BPD tend to show little positive and frequent negative facial affect, it is possible that BPD targets in this sample did so, too, and that raters have used this to inform their judgments. Future studies are needed to determine whether facial affect is indeed the mediating cue in this relationship and whether this effect has any specificity for the BPD population by including clinical control groups. If this is the case, individuals with BPD (and other types of psychopathology) might greatly benefit from interventions tailored towards increasing positive affect display and overall impression management.
Keywords: Hochschulschrift